2015
DOI: 10.1007/s10826-015-0278-4
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Social Competence Interventions for Children with Learning Disabilities

Abstract: Challenges in social competence are common in children with Learning Disabilities (LDs), particularly those who present with co-occurring mental health challenges (LD ? MH). Social competence calls upon a complex set of skills, including social skills, perspective-taking abilities, and an understanding of the social environment. Successful enactment of these skills necessitates behavioral and emotion regulation, an area of weakness for many youth with LD ? MH. Using a mixed-method design, the present study ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 54 publications
1
6
0
2
Order By: Relevance
“…Executive functioning deficits have been shown to be concurrently associated with poor emotion regulation and self-control (Barkley, 1997; Fino et al, 2014; Vaughn, DeLisi, Beaver, & Wright, 2009; Zelazo & Cunningham, 2007). Similarly, children with learning problems, especially those with ADHD (Wiener, 2004), demonstrate lower levels of self-regulation than typically developing peers (Bauminger & Kimhi-Kind, 2008; Milligan, Phillips, & Morgan, 2015).…”
Section: Mediators and Moderatorsmentioning
confidence: 99%
“…Executive functioning deficits have been shown to be concurrently associated with poor emotion regulation and self-control (Barkley, 1997; Fino et al, 2014; Vaughn, DeLisi, Beaver, & Wright, 2009; Zelazo & Cunningham, 2007). Similarly, children with learning problems, especially those with ADHD (Wiener, 2004), demonstrate lower levels of self-regulation than typically developing peers (Bauminger & Kimhi-Kind, 2008; Milligan, Phillips, & Morgan, 2015).…”
Section: Mediators and Moderatorsmentioning
confidence: 99%
“…As noted above, although the large majority of youth with ADHD also have learning disabilities (Mayes et al, 2000), patterns found in the present study may differ in youth with ADHD without learning challenges. Specifically, youth with both learning difficulties and mental health challenges may have greater difficulties with both executive functioning and emotion regulation than youth without these comorbid challenges (Milligan, Badali, & Spiroiu, 2015; Milligan, Phillips, & Morgan, 2015), which may be an interesting area for future investigation. Finally, the grand-averaged waveforms for the present study (see Figures 1 and 2) suggest that within- and between-group differences may be present in other components, particularly the P2.…”
Section: Discussionmentioning
confidence: 99%
“…According to the survey, before the learning intervention, the number of submitted assignments was 275, but after the intervention, the number of submissions reached 352, and the same change was found in self-evaluation and others' evaluation, which changed from 172 to 300, and self-evaluation changed from 233 to 349. In terms of discussion and communication, it was 72 in the first four weeks, but after the intervention, it reached 300, and learning resources changed from 95 to 370, a very significant improvement, and after investigating online testing, it was found that the first four weeks were only 125, but the use of the online testing system reached 315 after the intervention, and through these data, it can be shown that although the period of investigation is different, it can be seen from the improvement of students' learning programs that the intervention guidance is very helpful in serving students and can help them to complete their learning tasks effectively [27]. According to the examination of factual knowledge in Figure 8, our investigation divided it into six modules: memory, comprehension, application, analysis, evaluation, and creation, and according to the data, it is clear that in memory, there is a relatively significant improvement from 10 to 15 after the learning intervention; in analysis and evaluation creation, there is an improvement, but it is not significant, and in comprehension and application, the learning intervention has almost no effect.…”
Section: Information Fusion and Its Intelligentmentioning
confidence: 99%